The Mercantilist Index of Trade Policy. - Anderson, J; Neary, J (Blackwell Publishing, 2003)
We introduce an index of trade policy restrictiveness defined as the uniform tariff that maintains the same trade volume as a given tariff/quota structure. Our index overcomes the problems of the trade-weighted average tariff: It avoids substitution bias, correctly accounts for general equilibrium transfers, and takes import volume instead of welfare as benchmark. Empirical applications to international cross section and time-series comparisons of trade policy confirm our theoretical results: Trade-weighted average tariffs generally underestimate the true height of tariffs as measured by the trade-volume-equivalent index; this in turn always underestimates the welfare-equivalent index.